THE STRUCTURE OF HORIZONTAL RELATIONSHIPS IN NETWORK - Diniz Pereira, Breno Augusto (2013)
Interorganizational relationships in networks aim at improving the capacity of organizations in their interdependent relations, trying to improve organizational effectivity. This paper aims at identifying how organizations structure themselves in their interorganizational relations, in a way to contribute for the consolidation of the present theory. To perform this analysis, a study was carried out in companies which belong to five different types of horizontal networks. Data was collected through 28 interviews and 135 questionnaires, applied in companies located in 25 different cities in the state of Rio Grande do Sul. Results demonstrate that the networks were created as a strategy to survive in the marketplace. Variables such as innovation and learning were not considered as determinants for entering the network. Companies in networks acquire their initial benefits from the association, but they are not concerned about acquiring new knowledge. Therefore, it’s possible to observe an initiative to form networks with certain characteristics related to growth and protection against possible environmental changes.